2018
DOI: 10.1021/acsami.8b02367
|View full text |Cite
|
Sign up to set email alerts
|

Molecular O2 Activation over Cu(I)-Mediated C≡N Bond for Low-Temperature CO Oxidation

Abstract: The activation of molecular oxygen (O) is extremely crucial in heterogeneous oxidations for various industrial applications. Here, a charge-transfer complex CuTCNQ nanowire (CuTCNQ NW) array grown on the copper foam was first reported to show CO catalytic oxidation activity at a temperature below 200 °C with the activated O as an oxidant. The molecular O was energetically activated over the Cu(I)-mediated C≡N bond with a lower energy of -1.167 eV and preferentially reduced to O through one-electron transfer du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…There is no denying that molecular oxygen activation (MOA), the rate-determining step for photoinduced oxidation reactions on the photocatalyst surface, plays a pivotal role in the light-driven oxidation process especially in ROS generation. As such, extensive regulation strategies have been applied to modify photocatalysts to promote MOA such as defect engineering, ultrathin structure, and metal deposition . For example, Zhang and his group confirmed that oxygen vacancies (OVs) on BiOCl enable MOA to produce superoxide radicals ( • O 2 – ) in a side-on bridging mode .…”
Section: Introductionmentioning
confidence: 99%
“…There is no denying that molecular oxygen activation (MOA), the rate-determining step for photoinduced oxidation reactions on the photocatalyst surface, plays a pivotal role in the light-driven oxidation process especially in ROS generation. As such, extensive regulation strategies have been applied to modify photocatalysts to promote MOA such as defect engineering, ultrathin structure, and metal deposition . For example, Zhang and his group confirmed that oxygen vacancies (OVs) on BiOCl enable MOA to produce superoxide radicals ( • O 2 – ) in a side-on bridging mode .…”
Section: Introductionmentioning
confidence: 99%
“…The gold–CO interaction that may commonly exist in heterogeneous catalysis can influence the reactivity of the gold catalyst, and the AuCO unit can be dynamically generated under reaction conditions. However, the mobility of the whole AuCO unit during the catalysis of CO oxidation has not been discovered in previous gas-phase studies. Herein, by studying the reactions of neutral HMOCs in catalytic CO oxidation, we identified that CO adsorption can promote the mobility of the AuCO unit.…”
Section: Resultsmentioning
confidence: 99%
“…17 The activation of molecular O 2 on the surface of heterogeneous catalysts is the key step in different oxidation reactions, such as epoxidation and CO-, hydrocarbon-, alcohol-, and glucoseoxidations. 18 However, oxidation reactions using molecular O 2 oxidant oen have several challenges: (1) the direct oxidation of organic substrates using molecular O 2 typically occurs at harsh conditions (toxic solvents, high temperature, and high pressure); (2) a co-reductant is normally required to complete the oxidation of transition metal-based catalysis; and (3) product selectivity is relatively moderate. 18,19 Likewise, hydrogen peroxide has been studied as it also generates water as its byproduct.…”
Section: Oxygen Atom Sourcesmentioning
confidence: 99%
“…18 However, oxidation reactions using molecular O 2 oxidant oen have several challenges: (1) the direct oxidation of organic substrates using molecular O 2 typically occurs at harsh conditions (toxic solvents, high temperature, and high pressure); (2) a co-reductant is normally required to complete the oxidation of transition metal-based catalysis; and (3) product selectivity is relatively moderate. 18,19 Likewise, hydrogen peroxide has been studied as it also generates water as its byproduct. Fe-, Mn-, Rh-, W-, and Ti-based catalytic systems are known for employing H 2 O 2 as the terminal oxidant.…”
Section: Oxygen Atom Sourcesmentioning
confidence: 99%